Antioxidant, Antibacterial Activities and Synergistic Effect with Antibiotics of Fruits and Stems Extracts from Styphnolobium japonicum (L.) Schott - Karima Saffidine; Fatima Zerargui; Thoraya Guemaz; Charafeddine Lameche; Farida Sahli; Abderahmane Baghiani (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to evaluate the antioxidant and antibacterial properties of Styphnolobium japonicum (L.) Schott extracts. Results showed that the total phenols and flavonoids contents of the extracts ranged from 24.57 to 316.11 mg GAE/g and from 1.80 to 12.41μg QE/mg, respectively. Ethyl acetate (EaES) and aqueous (AqES) extracts from seeds showed the highest DPPH scavenging capacity (IC50= 5.51 and 23.43 μg/mL). EaES from seeds, stem bark and fruit pod were the most active in inhibiting β-carotene oxidation. While, aqueous extracts have the ability to chelate ferrous ions. Significant antibacterial activity was obtained against Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, Salmonella typhimurium, Listeria monocytogenes, Bacillus cereus and Pseudomonas aeroginosa; and inhibition zones varied between 10 to 29.5 mm. MIC and MBC ranged from 0.7–11.25 mg/mL and 5.63–22.5 mg/mL, respectively. In addition, synergistic effects were obtained, where inhibition zones varied between 7 and 50 mm. These results support the use of this species in traditional medicine in many physiological disorders and could be used where antioxidant and antibacterial are warranted.